Productivity Growth and Sustainability in Post-Green Revolution Agriculture : The Case of the Indian and Pakistan Punjabs - Murgai, Rinku; Ali, Mubarik; Byerlee, Derek (Washington, DC: World Bank, 2014)
This article attempts to determine the long-term productivity and sustainability of irrigated agriculture in the Indian and Pakistan Punjabs by measuring trends in total factor productivity for production systems in both states since the advent of the green revolution. These measurements over time and across systems have resulted in three major findings. First, there were wide spatial and temporal variations between the two Punjabs. Although output growth and crop yields were much higher in the Indian Punjab, productivity growth was higher by only a small margin. Moreover, the lowest growth in productivity took place during the initial green revolution period and in the wheat-rice system in both states. The time lag between adoption of green revolution technologies and realization of productivity gains is related to learning induced efficiency gains, better utilization of capital investments over time, and problems with the standard methods of productivity measurement that downwardly bias estimate, particularly during the green revolution period. Second, input growth accounted for most of the output growth in both Punjabs during the period under study. Third, intensification, especially in the wheat-rice system, resulted in resource degradation in both Punjabs. Data from Pakistan show that resource degradation reduced overall productivity growth from technical change and from education and infrastructure investment by one-third.